International network of cancer genome projects - Hudson, Thomas J.; Eils, Roland; Korbel, Jan Oliver; Korshunov, Andrey; Pfister, Stefan; Kalle, Christof von; Lichter, Peter; Brors, Benedikt; Radlwimmer, Bernhard (Nature, 2010)
Hundreds of individual human cancer genome sequences are expected to be published in 2010, and thousands per year after that. The International Cancer Genome Consortium (ICGC) was launched with the aim of keeping track of the data relating to large-scale cancer genome studies of all major cancers in adults and children — a total of 50 different cancer types and/or subtypes. In this issue the ICGC team (http://www.icgc.org) spells out the policies and planning for the project.